Meow - Raschka, Christopher (Greenwillow Books, an imprint of HarperCollins Publishers, 2022)
In this story--told almost entirely in the cat's meows--a young girl steps on her cat Marigold's tail, the hurt cat runs for cover, and after an apology, all is forgiven.